(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2021)
It was clear that the US-Turkish relations were of a distinctive privacy, which obliged it to decide about the options of dispute between them. If it were true for the independence of Turkey’s foreign policy in its regional area might contradict with the US and its interests, then it might push it to force it to do otherwise through using some pressure files on Turkey. The US pushed Turkey to move using several means; it exaggerated the (Communist danger) to Turkey, describing it as it was awaiting the appropriate moment to strike Turkey, in addition to the western media’s continious talks about such a danger so as to create a suitable condition for the Turks to make then enter into the US strategy. The US realized the importance of the Turkish role in the Middle East. This strategic importance is for seversl reasons, including Turkey’s geopolitical location (among three continents; Europe, Asia and Africa) connecting Turkey to many areas of US interest. Turkey is connected to the areas of the Middle East, Balkan, Caucas, Black Sea and Middle Asia by economic, cultural, and historical links. It also controls the sea passages which are of top priority for the US economic, political and military interests.